Hepatoprotective Activity of Hibiscus Flowers (Hibiscus rosa-sinensis) and Soursop Leaves (Annona muricata) Mix Infusion in Mus musculus Post Hyperuricemia Induction - Dian Fita Lestari; Vestidhia Yunisya Atmaja; Fatimatuzzahra Fatimatuzzahra; Shahnaz Shabrina Wulansari; Eliza Febrianti (Universitas Labuhanbatu, 2025)
Background: Liver has many functions in the metabolic system and detoxification of substances that are harmful to the body. Chemical intoxication due to drug use might induce liver damage. A histology examination can indicate liver damage induced by a chemical substance, as well as the condition of tissue structure and function associated with the disease. This study aims to investigate the hepatoprotective effect of mix infusion of hibiscus flowers and soursop leaves on the liver histological structure in mice induced by hyperuricemia using potassium oxonate. Methodology: This study used an experimental group design, involving 8-week-old mice. The groups were divided as follows: A1 (control), A2 (Potassium oxonate), A3 (allopurinol), A4 (infusion 25 %), A5 (infusion 35 %), and A6 (infusion 45 %). Histological image was examined using an optilab with five fields of view. Findings: The study's revealed that the control group had a normal liver histology structure, whereas the hyperuricemia treatment group experienced significant liver damage, including congestion and leukocyte infiltration, and the allopurinol treatment group experienced significant damage, including leukocyte infiltration and necrosis. Therapy with a combined infusion of hibiscus flowers and soursop leaves shown a hepatoprotective effect. Based on histological analysis, the 25 % concentration provided the greatest hepatoprotective impact when compared to other infusion concentration. Mix infusion of hibiscus flowers and soursop leaves demonstrates heproprotective activity in hyperuricemia mice induced by potassium oxonate. Contribution: This study demonstrates that the mix infusion of hibiscus flowers and soursop leaves has the potential to be a hepatoprotective agent, but further research is needed regarding long-term effects